A spear of summer grass - Raybourn, Deanna (Harlequin Mira, 2013)
Exiled to Kenya after her latest scandalous exploit, Delilah Drummond, now the mistress of her step-father's crumbling estate, falls into the decadent pleasures of society until she meets Ryder White who becomes her guide to the beauty of this complex world. Set in 1920s British Kenya.